2015
DOI: 10.1177/1934578x1501001229
|View full text |Cite
|
Sign up to set email alerts
|

New Benzenoids from the Roots of Lindera aggregata

Abstract: Two new benzenoids, linderagatin A and B (1-2), were isolated from the roots of Lindera aggregata. Their structures were elucidated on the basis of 1D ( 1 H, 13 C) and 2D NMR (COSY, NOESY, HSQC and HMBC) spectra. Moreover, their absolute configurations were established from ECD spectra compared with previous reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition to the above-mentioned extensive components in L. aggregata , there are also several other rare components, including 2 benzenoids (13–14), a benzene-type glycoside (15), 3 lindera cyclopentenedione derivatives (16–18), 3 bi-linderone derivatives (19, 20a, 20b), a butenolide (21), 3 lignans (22–24), 10 phenolics (25–34) and a linderaspirone (35) ( 16 , 39 , 54 , 55 ). They also demonstrate good pharmacological activities, such as compound 21 has anti-tumor activity, and compounds 19 and 35 show good anti-diabetic properties due to their significant insulin resistance alleviation ( 55 57 ).…”
Section: Chemical Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above-mentioned extensive components in L. aggregata , there are also several other rare components, including 2 benzenoids (13–14), a benzene-type glycoside (15), 3 lindera cyclopentenedione derivatives (16–18), 3 bi-linderone derivatives (19, 20a, 20b), a butenolide (21), 3 lignans (22–24), 10 phenolics (25–34) and a linderaspirone (35) ( 16 , 39 , 54 , 55 ). They also demonstrate good pharmacological activities, such as compound 21 has anti-tumor activity, and compounds 19 and 35 show good anti-diabetic properties due to their significant insulin resistance alleviation ( 55 57 ).…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…LA-R extract is the primary natural source of alkaloids. Thirty-seven alkaloids (1-37) have been successfully identified from L. aggregata, including 15 aporphine alkaloids (1-15), 8 benzyl tetrahydroisoquinoline alkaloids (16)(17)(18)(19)(20)(21)(22)(23), 2 morphinan alkaloids (24,25), 5 bis-benzyl tetrahydroisoquinoline alkaloids (26)(27)(28)(29)(30), a β-carboline alkaloid (31) and 6 amides (32-37) (13,16,24,(36)(37)(38)(39)(40)(41)(42)(43). Their structures and molecular formulae are shown in Table 2 and Figure 3.…”
Section: Alkaloidsmentioning
confidence: 99%
“…5. Ma et al (2015) managed to isolate two new benzenoids, identified as linderagatin A and B (100-101), together with three known lignans, rel-(2α,3β)-7-Omethylcedrusin (97), (-)-lyoniresinol (98), and evofolin B (99) from the roots part.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%